Analysis of Effect of Nitrogen Implus GTAW Welding Pipe Material SUS 304 - Dony Perdana; Moch. Nahrul Afan I (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
Tungsten Inert Gas welding is one of the widel y used techniques for joining ferrous and non-ferrousmetals. TIG welding process offers several advantages like joining of unlike metals, low heat effected zone, absence of sl ag etc compared to MIG welding. The accuracy and qualit y of welded joints lar gel y depends upon ty pe ofpower supply (DCSP or DCRP), welding speed, ty pe of inert gas used for shieldi ng. This paper deals with t he investigation of effect of use nitrogen gas to weld results. A good weld and flat was obtained. The conditions inside wall of the pipe has been welded kept clean without droppings and invisible residual welds attached. The results of x-ray can be saw great results no cavities, photograph obtained for welding use the nitrogen gas welding impulses better results because of its shape at the corner V filled or no weld defects in the weld metal.Keywords: TIG welding, SUS 304, impulse nitrogen, x-ray